Earnings Management and Capital Resource Allocation: Evidence from China's Accounting-Based Regulation of Rights Issues - Chen, Kevin C. W.; Yuan, Hongqi (The Accounting Review, 2004)
From 1996 to 1998, listed companies in China were required to achieve a minimum return on equity (ROE) of 10 percent in each of the previous three years before they could apply for permission to issue additional shares. As a result of this rule, there was a heavy concentration of ROEs in the area just above 10 percent. We show that the Chinese regulators appear to have scrutinized firms using excess amounts of nonoperating income to reach the 10 percent hurdle. In addition, their ability to do so seems to have improved over time, which allows them to be better able to identify firms that subsequently performed better. However, many firms were still able to gain rights issue approval through excess nonoperating income. We show that these firms subsequently underperformed other approved firms that did not use the same practice, indicating that the Chinese regulators' objective of guiding capital resources toward the well-performing sectors is partially compromised by earnings management.